Coming to terms with security : a lexicon for arms control, disarmament and confidence-building - Tulliu, Steve (UNIDIR, 2003)
"This glossary provides clear and precise definitions of arms control terms and places them in a historical context. It introduces the reader to the primary themes and concepts in the field of arms control and explains relevant terminology. The publication looks at the major arms control and disarmament agreements related to conventional, biological, chemical and nuclear weapons. The information is presented in English and Spanish."--Publisher description.